Utilizing Minutia Density Distribution and the Desmos Service for Fingerprint Wrinkle Detection (Eurasian Scientific Herald, 2023)
Fingerprint recognition is one of the safe methods that may be utilized to identify individuals automatically. It has garnered a lot of interest and is being used extensively in a variety of civilian applications, such as finance and access control, amongst other things. One of the primary components in image processing applications is a fingerprint, which refers to human attributes used for user authentication. Wrinkles destroy the structure and texture of a fingerprint, notably by severing ridgelines and creating a sequence of spurious minutiae. The presence of wrinkles is fatal to the structure and texture of a fingerprint. Therefore, creases make fingerprint recognition methods less accurate, particularly the method that is now considered the most reliable based on minutiae matching. In this paper, we investigate the detection of wrinkles from fingerprint images, including two aspects that handle wrinkles and reconstruct ridges. First, the distance between pseudo-minutiae pairings is calculated. Then, shelves are rebuilt utilizing Newton polynomial interpolation and the online service desmos. In the paper, results are presented